Scoping review on prevention of suicidal thoughts and behaviors in adolescents: methods, effectiveness and future directions - Josée Aoun; Michel Spodenkiewicz; Michel Spodenkiewicz; Michel Spodenkiewicz; Catherine Marimoutou (Frontiers in Child and Adolescent Psychiatry)
IntroductionDespite the extensive implementation of suicide prevention strategies targeting suicidal thoughts and behaviors (STB) in adolescents, there remains a concerning lack of improvement in the situation. In this comprehensive scoping review, our objective was to provide insights into prevention methods for suicidal thoughts and behaviors directed towards adolescents, including their effectiveness, public perception, and potential adaptations.MethodA scoping review was conducted, encompassing 71 articles including systematic review, clinical trials and qualitative studies for a wider understanding. Most articles included focus generally on adolescents aged 10–20.ResultsNo single intervention has shown expected effectiveness, collective efforts have laid a solid foundation for suicide prevention. Promising interventions include cognitive-behavioral therapy (CBT) and incorporating Technology-based interventions. However, challenges persist in promoting help-seeking behaviors and addressing barriers such as stigma, the natural impulsive nature of adolescents and difficulty in selecting and defining data and designs.DiscussionThis review underscores the need for a holistic approach to suicide prevention, integrating social, emotional, and psychological dimensions. Successful interventions target underlying issues like depression and loneliness rather than solely focusing on suicidal thoughts and behaviors (STB). Combining direct and indirect interventions is a sensible approach for both immediate and long-term results. Understanding Generation Z's unique needs, influenced by technology and diverse perspectives, is crucial for effective prevention.ConclusionInvolving adolescents and adopting patient-centered healthcare with outcome measures like Patient Perceived Outcome Measures can enhance suicide prevention efforts by prioritizing safety and patient experiences.